Legal Protection Notary/PPAT Regarding False Information Submitted by Consident in Deed of Sale and Purchase - Fakhrudin, Muhamad Rafi; Bonaprapta , Gandjar Laksmana (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
This study analyse Notary/PPAT responsibilities and protection effort law for Notary/PPAT against false information submitted by the consident in the deed of sale and purchase. Use study juridical normative, this research find that PPAT is responsible answer full to deed they made, description falsehoods conveyed by the facers fully become not quite enough answered the presenters, while PPAT was inside matter there is no responsible answer or not can requested not quite enough sue on losses incurred from exists information false facing. Notary/PPAT required get protection law and the Regional MKN must give agreement because, testimony from the relevant Notary/PPAT is required in make bright something cases carried out by a Notary in accordance with Article 66 paragraph (1) UUJN.